2023
DOI: 10.3390/ijms24065839
|View full text |Cite
|
Sign up to set email alerts
|

Dioleoylphosphatidylglycerol Inhibits Heat Shock Protein B4 (HSPB4)-Induced Inflammatory Pathways In Vitro

Abstract: Our previous work shows that dioleoylphosphatidylglycerol (DOPG) accelerates corneal epithelial healing in vitro and in vivo by unknown mechanisms. Prior data demonstrate that DOPG inhibits toll-like receptor (TLR) activation and inflammation induced by microbial components (pathogen-associated molecular patterns, PAMPs) and by endogenous molecules upregulated in psoriatic skin, which act as danger-associated molecular patterns (DAMPs) to activate TLRs and promote inflammation. In the injured cornea, sterile i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Less well known is the fact that TLR2 also requires CD14 [ 90 , 91 , 92 ]. Indeed, we recently showed that a CD14-blocking antibody inhibited the activation of both TLR4 and TLR2 in response to PAMPs and DAMPs [ 93 ]. Kuronama et al [ 12 ] found that both CD14 and MD-2 can bind PG, and they have suggested that this binding interferes with the ability of these accessory proteins to bind microbial components such as LPS, thus inhibiting their capacity to promote TLR activation [ 94 ].…”
Section: Dopg and Its Potential Beneficial Effects In Healing Of Chro...mentioning
confidence: 99%
See 2 more Smart Citations
“…Less well known is the fact that TLR2 also requires CD14 [ 90 , 91 , 92 ]. Indeed, we recently showed that a CD14-blocking antibody inhibited the activation of both TLR4 and TLR2 in response to PAMPs and DAMPs [ 93 ]. Kuronama et al [ 12 ] found that both CD14 and MD-2 can bind PG, and they have suggested that this binding interferes with the ability of these accessory proteins to bind microbial components such as LPS, thus inhibiting their capacity to promote TLR activation [ 94 ].…”
Section: Dopg and Its Potential Beneficial Effects In Healing Of Chro...mentioning
confidence: 99%
“…HMGB1 is reportedly a DAMP [ 131 ], functioning to activate pattern recognition receptors such as TLR4. In a recent study, we showed that HMGB1 activated TLR4, as monitored using a reporter cell line; importantly, DOPG inhibited TLR4 activation induced by HMGB1 [ 93 ]. In addition, several TLRs, including TLR2 and TLR4, are up-regulated in diabetic wounds, and TLR2- and TLR4-deficient knockout mice show accelerated wound healing [ 46 ].…”
Section: Dopg and Its Potential Beneficial Effects In Healing Of Chro...mentioning
confidence: 99%
See 1 more Smart Citation